2018 IEEE Global Conference on Signal and Information Processing (GlobalSIP) 2018
DOI: 10.1109/globalsip.2018.8646403
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive CSP for User Independence in Mi-Bci Paradigm for Upper Limb Stroke Rehabilitation

Abstract: A 3-class motor imagery (MI) Brain-Computer Interface (BCI) system, that implements subject adaptation with short to non-existing calibration sessions is proposed. The proposed adaptive common spatial patterns (ACSP) algorithm was tested on two datasets (an open source data set (4-class MI), and an in-house data set (3-class MI)). Results show that when long calibration data is available, the ACSP performs only slightly better (4%) than the CSP, but for short calibration sessions, the ACSP significantly improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Active training with autonomous involvement has been made possible by monitoring electromyography (EMG) signals in the affected foot. Recent interest in upper limb rehabilitation has included electroencephalography (EEG) monitoring, including the proposal of several motor imagery (MI) based rehabilitation systems [6], [7], [8]. A clinical study showed substantial improvement of arm motor function in an MI rehabilitation group, compared to a passive control group [9].…”
Section: Introductionmentioning
confidence: 99%
“…Active training with autonomous involvement has been made possible by monitoring electromyography (EMG) signals in the affected foot. Recent interest in upper limb rehabilitation has included electroencephalography (EEG) monitoring, including the proposal of several motor imagery (MI) based rehabilitation systems [6], [7], [8]. A clinical study showed substantial improvement of arm motor function in an MI rehabilitation group, compared to a passive control group [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Figure 14, interpolation provided comparable classification accuracies between the measured and combined groups of electrodes in one participant (S6), while the interpolated groups of electrodes showed poorer classification accuracies for most participants. According to other studies [34,36,38,81], ERD/ERS phenomena are participantspecific, whereby phenomena can occur in different positions and different frequencies for each participant. This may be explained by the corresponding brain area that contains meaningful information for classifying the left-and right-hand opening/closing task in participant S6 that was not part of the interpolated channels.…”
Section: Discussionmentioning
confidence: 97%